(untitled) (The Pretoria Student Law Review, 2023)
In this article, I reflect on the idea of a ‘post’-apartheid South African constitutionalism and the related and implicated notion of Transformative Constitutionalism by emphasising its continued bondage to a colonial and apartheid past. In an effort to critically explore the ‘post’-apartheid transformative constitutional framework, I examine the endurance of colonialism as coloniality in the manner it has unfolded in the South African context. This exploration involves highlighting three constitutive elements of this endurance: linear historicism as observed in Hobbes’ social contract; the geography of reason as theorised by Schmitt; and the lines within South African society and knowledge systems as a result of what De Sousa Santos calls ‘abyssal thinking’. Although the endurance of historical colonialism as coloniality can be described in a number of ways, I deal with these specific constitutive elements in order to argue that the doctrine of transformation, which includes Transformative Constitutionalism, has largely been ineffective in its attempt to eradicate coloniality as it has failed to achieve epistemic justice for the majority of (South) Africans. I conclude by suggesting that the doctrine of transformation and, as such, Transformative Constitutionalism has served to further exclude and marginalise the knowledge of indigenous (South) African people in the ‘post’-apartheid constitutional dispensation. The project of transformation has sustained the abyssal line as it has been internalised through coloniality. As such, the ‘post’-apartheid South African dispensation remains divided by this line — essentially discarding indigenous (South) African people and their knowledge systems to the abyss. I further argue that the persistence of coloniality, sustained by the abyssal line, requires a project of conceptual decolonisation if coloniality and epistemic injustice is to be undone. In this sense, a true (South) African dispensation may be disclosed.